WAIS Divide Microparticle Concentration and Size Distribution, 0-2400 ka - Koffman, Bess; Kreutz, Karl (IEDA: US Antarctic Program Data Center, 2015)
This data set includes raw dust microparticle data for the WAIS Divide deep core, WDC06A, from the surface to 577 m. Data were collected in 2010 using a Klotz Abakus laser particle counter connected to a continuous ice core melter system at the University of Maine (Breton et al., 2012).